Lipoprotein aggregation protects human monocyte-derived macrophages from OxLDL-induced cytotoxicity - Reto Asmis; Jim G. Begley; Jennifer Jelk; William V. Everson (Journal of Lipid Research, 2005)
Oxidative modifications render low density lipoprotein cytotoxic and enhance its propensity to aggregate and fuse into particles similar to those found in atherosclerotic lesions. We showed previously that aggregation of oxidized LDL (OxLDL) promotes the transformation of human macrophages into lipid-laden foam cells (Asmis, R., and J. Jelk. 2000. Large variations in human foam cell formation in individuals. A fully autologous in vitro assay based on the quantitative analysis of cellular neutral lipids. Atherosclerosis. 148: 243–253). Here, we tested the hypothesis that aggregation of OxLDL enhances its clearance by human macrophages and thus may protect macrophages from OxLDL-induced cytotoxicity. We found that increased aggregation of OxLDL correlated with decreased macrophage injury. Using 3H-labeled and Alexa546-labeled OxLDL, we found that aggregation enhanced OxLDL uptake and increased cholesteryl ester accumulation but did not alter free cholesterol levels in macrophages. Acetylated LDL was a potent competitor of aggregated oxidized LDL (AggOxLDL) uptake, suggesting that scavenger receptor A plays an important role in the clearance of AggOxLDL. Inhibitors of actin polymerization, cytochalasin B, cytochalasin D, and latrunculin A, also prevented AggOxLDL uptake and restored OxLDL-induced cytotoxicity. This suggests that OxLDL-induced macrophage injury does not require OxLDL uptake and may occur on the cell surface.Our data demonstrate that aggregation of cytotoxic OxLDL enhances its clearance by macrophages without damage to the cells, thus allowing macrophages to avoid OxLDL-induced cell injury.